"Finally Something for Us": Black Girls Run! and Racialized Space-Making in Recreational Running. (June 2021) - Smith-Tran, Alicia
This study uses life story interviews to understand the utility of Black Girls Run!—a predominantly Black organization for women who engage in recreational distance running. Drawing from Neckerman, Carter, and Lee's conceptual framework of the minority culture of mobility, the author suggests that Black Girls Run! serves the purpose of helping its members confront the challenges and repercussions associated with being a racial minority in a majority White space, particularly as they are experienced by middle-class Black women. The author focuses on how the organization (a) allows its members to run with others who look like them, (b) cultivates social connection and community, and (c) facilitates challenging health statistics and shifting dominant narratives about Black women. This study provides a more nuanced understanding of the latent functions of recreational sporting organizations catered to middle-class people of color.